2022
DOI: 10.1039/d1cp05745f
|View full text |Cite
|
Sign up to set email alerts
|

What quantum chemical simulations tell us about the infrared spectra, structure and interionic interactions of a bulk ionic liquid

Abstract: The recently developed efficient protocol to explicit quantum mechanical modeling of structure and IR spectra of liquids and solutions [Katsyuba et al., J. Phys. Chem. B, 2020, 124, 6664-6670] is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In other words, we demonstrated that the vibrational modes and derivatives of the polarizability of a solute are mainly locally influenced by its immediate environment, while the effect of bulk water is rather modest. This is in parallel with the outcome of our liquid-state IR spectra simulations, 6,[8][9][10][11][12] which showed that the dipole moment derivatives of a solute are mainly locally influenced by its immediate surroundings. This knowledge not only improves our understanding of solute-solvent interactions, but also allows minimization of the computational costs of QM simulations of the liquid-state Raman spectra.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In other words, we demonstrated that the vibrational modes and derivatives of the polarizability of a solute are mainly locally influenced by its immediate environment, while the effect of bulk water is rather modest. This is in parallel with the outcome of our liquid-state IR spectra simulations, 6,[8][9][10][11][12] which showed that the dipole moment derivatives of a solute are mainly locally influenced by its immediate surroundings. This knowledge not only improves our understanding of solute-solvent interactions, but also allows minimization of the computational costs of QM simulations of the liquid-state Raman spectra.…”
Section: Discussionsupporting
confidence: 80%
“…Initially 6 we calculated the IR spectrum of any system, modeled within the framework of our cluster approach, as a thermodynamic average of the individual spectra computed for each complete cluster at the DFT level. Nevertheless, further studies [8][9][10][11][12] have shown that the difference between the spectrum of the lowest-energy cluster and that averaged from all clusters in the final ensemble is negligible, and hence the averaging was avoided to minimize computational expenses. The same turned out to be true for the present case, which is clearly seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…55 In previous studies 56 it has been suggested that vibrational modes and dipole moment derivatives are mainly influenced by their immediate local surroundings, which also holds for hydrogen bonded systems like ethanol, 57 aqueous and methanolic solutions of methyl lactate, 58 and ionic liquids. 59 The inclusion of the first solvation shell is deemed to be sufficient to simulate solution phase IR spectra with similar accuracy as for individual molecules in a vacuum. To simulate the dichloromethane clusters of solvated tautomers/conformers, 19 to 44 CH 2 Cl 2 molecules were added to each of the solute geometries.…”
Section: Computationsmentioning
confidence: 99%